1993
DOI: 10.1152/ajpheart.1993.265.2.h621
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen modulation of pulmonary arterial prostacyclin synthesis is developmentally regulated

Abstract: To better understand the role of prostacyclin [prostaglandin (PG) I2] in oxygen mediation of vasomotor tone in the developing lung, we determined the ontogeny of the direct effects of acute changes in oxygen on in vitro PGI2 synthesis and adenosine 3',5'-cyclic monophosphate (cAMP) production in intrapulmonary arteries from fetal and newborn lambs. In the absence of varying oxygen, PGI2 synthesis increased 6.9-fold from early to late in the third trimester, and it rose an additional 3.2-fold from late gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
2
24
0
1
Order By: Relevance
“…Although previous investigators have demonstrated a role for calcium release from ryanodine-sensitive stores in umbilical vein endothelial cells (25), the present data are the first to implicate a role for calcium release from ryanodinesensitive stores in the normoxia-induced increase in fetal PAEC [Ca 2ϩ ] i . At birth, PAECs must contract, increase production of NO (8,26) and prostacylin (27,28), and decrease endothelin production (29) to enable effective gas exchange to occur in the lungs. Changing the exposure of PAECs from normoxia to hypoxia reduces reactive oxygen species (ROS) (30,31) so presumably the reverse is also true.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous investigators have demonstrated a role for calcium release from ryanodine-sensitive stores in umbilical vein endothelial cells (25), the present data are the first to implicate a role for calcium release from ryanodinesensitive stores in the normoxia-induced increase in fetal PAEC [Ca 2ϩ ] i . At birth, PAECs must contract, increase production of NO (8,26) and prostacylin (27,28), and decrease endothelin production (29) to enable effective gas exchange to occur in the lungs. Changing the exposure of PAECs from normoxia to hypoxia reduces reactive oxygen species (ROS) (30,31) so presumably the reverse is also true.…”
Section: Discussionmentioning
confidence: 99%
“…By extension, ET-1 is implicated in the pulmonary constric-tor response to hypoxia [1]. Evidence in support of these concepts has also been obtained by other investigators using a variety of approaches both in vitro [6][7][8][9][10][11][12][13][14][15] and in vivo [15][16][17][18][19][20][21][22]. Nevertheless, the ontogeny of these regulatory mechanisms remains undefined despite the importance, both conceptual and practical, of the problem.…”
Section: Introductionmentioning
confidence: 89%
“…Увеличение ее содержания цАМФ вызывает релак сацию гладких мышц через фосфорилирование мио зина или активацию калиевых каналов, ведущую к гиперполяризации гладких мышц. Продукция простациклина значительно увеличивается в пос леднем триместре беременности [23], когда несколь ко эндотелий зависимых вазодилататоров, в т. ч. ацетилхолин и брадикинин, увеличивают его синтез в легких плода.…”
Section: онтогенез регуляторных механизмов легочной циркуляции в пренunclassified